Cerium oxide controllably modified noble metal-based porous carbon catalyst, preparation method and application
By loading cerium oxide in the pores of the porous carbon catalyst, the cerium oxide migration and dissolution problems are solved, and the stability and service life of the fuel cell are improved.
Patent Information
- Application Number
- CN202510073757.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-01-17
AI Technical Summary
In the existing fuel cell catalysts, cerium oxide has problems with migration and dissolution, resulting in weakening of free radical elimination capacity and decreasing proton conduction capacity, affecting the durability and service life of fuel cells.
By loading cerium oxide in the pores of the porous carbon catalyst, the migration and dissolution of cerium oxide is avoided by using the limiting effect of the pores, and it is close to the electrochemical reaction site, ensuring that it can quickly remove free radicals generated during power generation.
It effectively improves the stability and service life of the fuel cell, and reduces the increase in the hydrogen leakage current density of the proton exchange membrane and the proton conduction resistance of the catalytic layer.
Smart Images

Figure CN119786623A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of fuel cell catalysts, and in particular to a cerium oxide controllably modified noble metal-based porous carbon catalyst, a preparation method and an application thereof. Background Art
[0002] Hydrogen energy is considered to be the best carrier to solve the problem of seasonal fluctuations in renewable energy. As the best device to convert hydrogen energy into electrical energy, proton exchange membrane fuel cells (PEMFC) have become an ideal power source to replace internal combustion engines. Due to their advantages in mass power density and starting speed, fuel cells are oriented towards heavy-duty vehicles (HDV) in the future. In order to promote the commercialization of fuel cells in HDV, durability is an important indicator that needs to be overcome. The New Energy and Industrial Technology Development Organization (NEDO) of Japan has proposed that the service life of fuel cells should reach 50,000 hours in 2030. Among the key components of fuel cells, the proton exchange membrane and the ionomer in the catalyst layer are easily damaged by free radicals during operation, which weakens the hydrogen barrier effect and deteriorates the proton conductivity, causing serious durability problems.
[0003] In the prior art, free radical scavengers, such as cerium oxide, are often added to eliminate free radicals generated during operation. However, due to the problem of cerium oxide being lost with potential migration, the free radical elimination ability is weakened, and the dissolution of cerium ions will produce ion exchange with ionomers, resulting in a decrease in the proton conductivity of the ionomer. Therefore, it is necessary to develop a technology that effectively limits the migration and dissolution of cerium oxide, increase the action time of cerium oxide, and further improve the stability and service life of the fuel cell. Summary of the invention
[0004] The present invention aims to solve one of the technical problems in the related art at least to a certain extent.
[0005] To this end, the present invention proposes a cerium oxide controllably modified precious metal-based porous carbon catalyst, a preparation method and an application. The present invention loads cerium oxide in the pores of the porous carrier. The confinement effect of the pores can effectively avoid the migration of cerium oxide particles and slow down the dissolution of cerium ions. The cerium oxide is loaded on the carbon carrier close to the electrochemical reaction site, which can quickly remove the free radicals generated during the power generation process, effectively improving the stability and service life of the fuel cell.
[0006] In order to achieve the above object, the present invention adopts the following technical solution:
[0007] The first aspect of the present invention provides a cerium oxide controllably modified precious metal-based porous carbon catalyst, wherein cerium oxide particles are respectively loaded inside and outside the pores of the porous carbon, the cerium oxide particles loaded inside the pores are not less than 40% of the total loading amount of the cerium oxide particles in the porous carbon catalyst, the cerium / carbon mass ratio loaded on the porous carbon catalyst is 0.2:1 to 0.5:1, and the pore volume of the porous carbon used for loading is 0.4 cm 3 / g~1cm 3 / g.
[0008] In some embodiments, the noble metal-based particles are selected to provide electrochemical reaction activity.
[0009] In some embodiments, the material of the noble metal-based particles is any one of the following:
[0010] Any noble metal or alloy of multiple noble metals;
[0011] Alloys containing a noble metal element and at least one non-noble metal element;
[0012] Noble metal oxynitrides.
[0013] The second aspect of the present invention provides a method for preparing the porous carbon catalyst described in any embodiment of the first aspect of the present invention, comprising:
[0014] In the first step, the cerium source precursor and the noble metal-based porous carbon catalyst are fully dispersed and impregnated in the porous carbon pores;
[0015] In the second step, the cerium source is reacted inside and outside the pores of the porous carbon to generate cerium oxide, thereby completing the loading;
[0016] The third step is to separate and purify the modified catalyst from the reaction solution to obtain the cerium oxide controllably modified noble metal-based porous carbon catalyst.
[0017] In some embodiments, the dipping process in the first process is performed under an inert atmosphere and a set vacuum degree is maintained.
[0018] In some embodiments, the vacuum degree is set at -0.1 MPa to -0.02 MPa.
[0019] In some embodiments, the second step specifically includes: under stirring conditions, adding alkaline solution dropwise to adjust the pH to obtain a mixed dispersion, and reacting the cerium source inside and outside the pores of the porous carbon at a preset reaction temperature to generate cerium oxide to complete the loading.
[0020] In some embodiments, the pH is controlled at 10-14.
[0021] In some embodiments, the preset reaction temperature is set to 30°C to 70°C.
[0022] In some embodiments, the third step specifically comprises: filtering the product obtained in the second step, removing weakly durable ionic components, removing weakly durable non-ionic components, and drying to obtain the cerium oxide controllably modified noble metal porous carbon catalyst;
[0023] The weakly durable ion components are unreacted ionic substances on the catalyst surface and ionic substances generated during the oxide generation process;
[0024] The weakly durable non-ionic component is cerium oxide attached to the outside of the porous carbon pores and easily falling off, and cerium oxide particles not attached to the porous carbon;
[0025] Weakly durable ions and non-ionic components are removed to ensure that there are no ionic substances on the catalyst, and the cerium oxide loaded on the catalyst carbon carrier is mainly present in the pores, so that the durable effect has a long-term effect.
[0026] In some embodiments, both the removal of the weakly durable ionic components and the removal of the weakly durable non-ionic components are carried out by a combined treatment of deionized water washing and vacuum filtration.
[0027] In some embodiments, the removal of the weakly durable non-ionic components further includes applying mechanical vibration and stirring without damaging the catalyst particles.
[0028] A third aspect of the present invention provides a hydrogen fuel cell, which has an electrode catalyst layer, and the electrode catalyst layer includes the porous carbon catalyst described in any embodiment of the first aspect of the present invention and / or the porous carbon catalyst prepared in any embodiment of the second aspect of the present invention.
[0029] Compared with the prior art, the present invention has the following characteristics and beneficial effects:
[0030] The prior art often adds free radical scavengers, such as cerium oxide, to eliminate free radicals generated during operation. However, due to the problem of cerium oxide being lost with potential migration, the free radical elimination ability is weakened, and the dissolution of cerium ions will produce ion exchange with ionomers, causing the proton conductivity of ionomers to decrease. The present invention loads cerium oxide into the pores of a porous carbon catalyst, uses the catalyst to make an anode catalyst layer, and then makes a hydrogen fuel cell. After the endurance test under idle conditions, the increase in the hydrogen leakage current density of the proton exchange membrane used is reduced, and the increase in the proton conduction resistance of the catalyst layer is reduced. It can be considered that the reason is: during the endurance process, the dissolution and migration of cerium ions will affect the loss of the free radical elimination effect, and the sulfonic acid radicals of the perfluorosulfonic acid polymer will exchange ions with the dissolved cerium ions, affecting the proton conductivity. By limiting the cerium oxide particles in the pore structure of the noble metal-based porous carbon catalyst, the migration of the cerium oxide particles is avoided and the dissolution is slowed down, and the cerium oxide is close to the free radical generation site, which can eliminate the free radicals generated in the power generation reaction in real time, further improving the stability and service life of the fuel cell. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 The XPS results of the cerium oxide controllably modified noble metal-based porous carbon catalyst prepared in the embodiment of the present invention, wherein a and b are the full spectrum results and Ce element fine spectrum of embodiment 1, and c and d are the full spectrum results and Ce element fine spectrum of embodiment 2;
[0032] Figure 2 Figures a and b are the isothermal adsorption results of nitrogen before and after loading of Example 1 of the present invention, respectively;
[0033] Figure 3 The voltage decay rate during the endurance test of Example 3, Example 4, Comparative Example 2 and Comparative Example 3 of the present invention;
[0034] Figure 4 The changes in hydrogen leakage current density at the starting point and the end point of the endurance test of Example 3, Example 4, Comparative Example 2 and Comparative Example 3 of the present invention are shown;
[0035] Figure 5 The proton conduction resistance changes of the catalyst layer at the end point and the end point of the durability test of the proton conduction resistance of Example 3, Example 4, Comparative Example 2 and Comparative Example 3 of the present invention;
[0036] Figure 6 The polarization curve changes at the end point and end point of the durability test are shown in Figures 3 and 4 of the present invention, and Comparative Examples 2 and 3 are shown in Figures 3 and 4 of the present invention.
[0037] Figure 7When the power generation performance of Example 3, Example 4, Comparative Example 2 and Comparative Example 3 of the present invention is tested, the endurance starting point and end point are 1A·cm -2 Voltage variation at different current densities. DETAILED DESCRIPTION
[0038] The present application is further described in detail below by specific embodiments in conjunction with the accompanying drawings. Wherein similar elements in different embodiments adopt associated similar element numbers. In the following embodiments, many detailed descriptions are intended to enable the present application to be better understood. However, those skilled in the art can easily recognize that some of the features can be omitted in different situations, or can be replaced by other elements, materials, and methods. In some cases, some operations related to the present application are not shown or described in the specification, in order to avoid the core part of the present application being overwhelmed by too much description, and for those skilled in the art, it is not necessary to describe these related operations in detail, and they can fully understand the related operations based on the description in the specification and the general technical knowledge in the art.
[0039] In addition, the features, operations or characteristics described in the specification can be combined in any appropriate manner to form various implementations. At the same time, the steps or actions in the method description can also be interchanged or adjusted in a manner that is obvious to those skilled in the art. Therefore, the various sequences in the specification and the drawings are only for the purpose of clearly describing a certain embodiment and are not meant to be a required sequence, unless otherwise specified that a certain sequence must be followed.
[0040] The endpoints and any values of the ranges disclosed in this application are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this application.
[0041] The first aspect of the present invention provides a cerium oxide controllably modified precious metal-based porous carbon catalyst, wherein cerium oxide particles are respectively loaded inside and outside the pores of the porous carbon, and the cerium oxide particles loaded inside the pores are not less than 40% of the total loading amount of cerium oxide particles in the porous carbon catalyst, and the cerium / carbon mass ratio loaded on the catalyst is 0.2:1 to 0.5:1, and the pore volume of the porous carbon used for loading is 0.4cm 3 / g~1cm 3 / g, noble metal-based particles are used to provide electrochemical reaction activity.
[0042] Furthermore, when the amount of cerium oxide loaded in the pores is small, the quenching effect on the free radicals generated by the precious metal in the pores is weak, and the limiting effect on the loss of cerium oxide with potential migration is small, and the effect on increasing the action time of cerium oxide is not significant. Therefore, in the embodiment of the present invention, the cerium oxide particles loaded in the pores are limited to not less than 40% of the total loading of cerium oxide particles in the porous carbon catalyst. In principle, all cerium oxide particles can be loaded in the pores of the porous carbon, that is, the cerium oxide particles loaded in the pores account for 40% to 100% of the total loading of cerium oxide particles in the porous carbon catalyst, preferably set to 40% to 70%.
[0043] Furthermore, the cerium oxide deposited in the pores can be calculated by the nitrogen isotherm adsorption curves before and after loading, and the pore size, pore volume and BET specific surface area can be obtained by analyzing the difference between the two. Since the cerium oxide loaded outside the pores is easy to migrate and dissolve, and loses the durability effect, in order to improve the durability effect, the embodiment of the present invention loads a certain amount of cerium oxide particles inside the pores of the porous carbon. The confinement effect of the pores can effectively slow down the dissolution of cerium ions. The cerium oxide is loaded on the carbon carrier close to the electrochemical reaction site, which can quickly remove the free radicals generated during the power generation process, effectively improving the stability and service life of the fuel cell.
[0044] Furthermore, the cerium / carbon mass ratio used in the embodiment of the present invention is used to indicate the loading amount of cerium oxide, which is calculated by measuring the cerium element content and the carbon element mass ratio by X-ray photoelectron spectroscopy (XPS). If the cerium / carbon mass ratio is too small, the amount of cerium oxide is small, and the free radicals generated during the aging process will occupy the free radical capture site, resulting in incomplete free radical capture and aging. Therefore, the cerium / carbon mass ratio is preferably greater than 0.2:1; if the cerium / carbon mass ratio is too large, the amount of cerium oxide is large, which will cause excessive coverage of cerium oxide on the catalyst, resulting in the electrochemically active precious metal alloy being covered, affecting the supply of reaction gas and the transmission of protons. Therefore, the cerium / carbon mass ratio should preferably be less than 0.5:1. Therefore, in the embodiment of the present invention, the supported cerium / carbon mass ratio is set to 0.2:1 to 0.5:1.
[0045] Furthermore, the pore volume defined in the embodiments of the present invention refers to the volume of the pores inside the carrier carbon, excluding the volume of the interparticle accumulation. The pore volume is calculated by the BJH method using the adsorption branch of the nitrogen adsorption isotherm. If the pore volume is too small, it is not conducive to the pore loading of cerium oxide. Therefore, the pore volume should not be less than 0.4 cm 3 / g; If the pore volume is too large, the risk of ionomer invading the pores will increase, which will lead to reduced catalyst poisoning activity. Therefore, the pore volume should not be greater than 1cm 3 / g. Therefore, in the present embodiment, the pore volume of the porous carbon used for loading is set to 0.4 cm 3 / g~1cm 3 / g.
[0046] Furthermore, in the embodiments of the present invention, the noble metal-based particles are not particularly limited as long as they can catalyze hydrogen oxidation and oxygen reduction reactions. Examples of the materials of the noble metal-based particles include:
[0047] a. Precious metals (Pt, Pd, Rh, Ir, Au, Ag, Ru, Os, etc.), which can be a single precious metal or an alloy of a combination of multiple precious metals;
[0048] b. Alloys containing precious metal elements and one or more non-precious metal elements (Fe, Co, Cr, V, Ti, Ni, etc.);
[0049] c. Noble metal oxynitrides.
[0050] The second aspect of the present invention provides a method for preparing a noble metal-based porous carbon catalyst controllably modified with cerium oxide, comprising the following steps:
[0051] In the first step, the cerium source precursor and the catalyst are fully dispersed and impregnated in the pores of the porous carbon;
[0052] In the second step, the cerium source is reacted inside and outside the pores of the porous carbon to generate cerium oxide, thereby completing the loading;
[0053] The third step is to separate and purify the modified catalyst from the reaction solution to obtain a noble metal-based porous carbon catalyst controllably modified with cerium oxide.
[0054] In some embodiments, the first step is specifically as follows: fully dissolving the cerium source precursor in a solvent, adding a noble metal-based porous carbon catalyst, stirring and dispersing the catalyst evenly, and maintaining a vacuum degree after replacing the inert gas.
[0055] Furthermore, the cerium source precursor in the first step is selected from substances that can generate cerium oxide through reaction, and specifically at least one of cerium nitrate hexahydrate, cerium sulfate tetrahydrate and cerium chloride can be used.
[0056] Furthermore, the amount of the cerium source in the first step is calculated based on the mass of the cerium element, and the mass ratio of the cerium source to the porous carbon is 0.2:1 to 0.5:1. If the ratio is too low, the cerium / carbon mass ratio after loading is too low, resulting in insufficient free radical capture capability, so the ratio is preferably above 0.2:1; if the ratio is too high, the cerium / carbon mass ratio after loading is too high, which will cause excessive coverage of cerium oxide on the catalyst, resulting in the electrochemically active noble metal alloy being covered, affecting the supply of reaction gas and the transmission of protons, so the ratio is preferably below 0.5:1.
[0057] Furthermore, the solvent used in the first step can fully dissolve the cerium source precursor, facilitate the subsequent catalyst dispersion, and achieve a set surface tension so that the precursor solution can fully infiltrate the liquid system in the porous carbon pores. Specifically, at least one of water, ethanol, isopropanol and n-butanol can be selected.
[0058] Furthermore, the combination and minimum amount of solvents in the first step should be sufficient to dissolve the cerium source precursor, and the optimal combination and amount are selected according to the type of cerium source. The solvent combination and amount are preferably such that the catalyst system is evenly dispersed. The solution combination and amount are further preferably such that the set surface tension can be achieved so that the precursor solution can fully infiltrate the porous carbon pores.
[0059] Further, the inert gas in the first step is used for the reaction system to reduce the occurrence of side reactions and maintain an inert atmosphere to ensure safety, and specifically at least one of argon, helium, nitrogen and carbon dioxide can be selected. The inert gas replacement is completed after the original gas atmosphere in the reaction system is evacuated and discharged, and then the inert gas is introduced for a certain period of time. The time for evacuating and introducing the inert gas is preferably 3 minutes to 5 minutes, and the number of replacements is selected according to the vacuuming and ventilation time. The best number of times.
[0060] Furthermore, the vacuum degree in the first step refers to the vacuum state in the sealed reaction system. If the vacuum degree is too high, the gas in the porous carbon cannot be discharged, and the cerium source precursor solution cannot completely infiltrate the porous carbon, resulting in a low proportion of pores in the subsequent loading process. Therefore, the vacuum degree is preferably -0.1MPa to -0.02MPa.
[0061] In some embodiments, the second step (loading step) is specifically as follows: under stirring conditions, an alkaline solution is added dropwise to adjust the pH to obtain a mixed dispersion, and at a preset reaction temperature, the cerium source is allowed to react inside and outside the pores of the porous carbon for a certain period of time to generate cerium oxide, thereby completing the loading.
[0062] Furthermore, the alkaline solution used in the second step is used to provide an alkaline reaction system to react the cerium source precursor to generate cerium oxide. The alkaline solution can be prepared from at least one of sodium hydroxide and potassium hydroxide. The amount of the alkaline solution is determined according to the amount of solution in the actual reaction system, and the optimal amount of solution is selected based on the uniform dispersion of the alkaline solution after dropwise addition.
[0063] Furthermore, the pH value of the reaction system in the second step will affect the particle size of the cerium oxide generated by the reaction. The particle size of the cerium oxide needs to be controlled so that it can be loaded into the pores. The preferred pH value is 10-14.
[0064] Furthermore, the preset reaction temperature used in the second step affects the generation rate of cerium oxide. If the temperature is too high, the reaction rate is fast, and the generated cerium oxide is easy to agglomerate, which makes the particle size of cerium oxide larger, which is not conducive to loading into the pores. Therefore, the preset reaction temperature should not be higher than 70°C. On the other hand, if the temperature is too low, the reaction is difficult to cross the reaction energy barrier and cannot occur. Therefore, the preset reaction temperature should not be lower than 30°C. Therefore, the preset reaction temperature used in the second step is preferably set to 30°C to 70°C.
[0065] Furthermore, in the second step, if the reaction time is too short, it is difficult to completely generate cerium oxide. If the reaction time is too long, the economic efficiency of the synthesis method will be affected, and there may be a risk of side reactions. The specific reaction time is selected based on the state of the reaction system, such as temperature, pH, and material concentration of the reaction solution.
[0066] In some embodiments, the third step (post-processing step) is specifically as follows: the product obtained in the second step is filtered, weakly durable ionic components are removed, weakly durable non-ionic components are removed, and dried to obtain a cerium oxide controllably modified precious metal porous carbon catalyst.
[0067] Furthermore, in the third step, the catalyst generated by the reaction is preliminarily separated from the reaction solution by suction filtration. Optionally, the filter paper used for suction filtration is a nitrocellulose filter membrane, the specific model is: Whatman7182-002, 0.2 μm.
[0068] Furthermore, in the third process, the weakly durable ionic component refers to the unreacted ionic substances on the catalyst surface and the ionic substances generated during the oxide formation process. The ionic components do not contribute to durability, and will undergo ion exchange with the sulfonic acid groups of the ionic polymer in subsequent fuel cell applications, thereby reducing the proton conductivity of the ionomer. The removal of the above-mentioned weakly durable ionic components can be carried out by a combined treatment method of deionized water washing and vacuum filtration. The specific number of water washings, the vacuum filtration intensity, and the final treatment time are combined with the content of weakly durable ionic components in the reaction system to select the optimal process. The end point of water washing is that the filtrate is neutral. Whether the ionic substances are completely removed can be detected by measuring the resistivity of the filtrate, that is, the resistivity is close to the resistivity of the deionized water used in the embodiment (>18.3MΩ·cm).
[0069] Furthermore, in the third process, the weakly durable non-ionic component refers to the cerium oxide attached to the outside of the carbon carrier pores and easily falling off and the cerium oxide particles not attached to the carbon carrier. This component will dissolve during the durability process and migrate with the electric field, which is not conducive to the long-term effectiveness of the durability effect. The removal of non-ionic components can be carried out by a combination of deionized water washing and vacuum filtration, and enhanced separation operations can be used. Mechanical vibration and stirring processes can be applied without destroying the catalyst particles to separate the weakly durable non-ionic components from the catalyst into the filtrate. The appropriate size of the filter membrane pore size can ensure that the cerium oxide particles flow out with the filtrate and will not cause the catalyst to be lost. The specific number of water washings, vacuum filtration intensity, enhanced separation operation and final processing time are combined with the content of weakly durable non-ionic components in the reaction system to select the optimal process.
[0070] Furthermore, the drying in the third process is to use a vacuum oven to remove the water attached to the surface of the catalyst after water washing. The drying temperature should be set in an appropriate range. If the drying temperature is too high, the side reactions caused by the temperature may affect the activity of the catalyst, so the drying temperature should not be higher than 100°C; if the drying temperature is too low, the water is difficult to remove quickly, so the drying temperature should not be lower than 60°C. For the drying time, the optimal time is selected according to the drying temperature. In order to ensure safety and prevent problems such as catalyst fire, a certain inert gas atmosphere (such as nitrogen) needs to be maintained during the pressure recovery process after drying.
[0071] The third aspect of the present invention provides an application of a cerium oxide controllably modified noble metal-based porous carbon catalyst in a hydrogen fuel cell. The hydrogen fuel cell involved in the present invention uses at least the catalyst involved in the present invention as the catalyst of the anode catalyst layer. The composition of the anode catalyst layer (such as platinum loading, ionomer type, ionomer to carbon mass ratio (I / C ratio) etc.) is not particularly limited, and the optimal value can be selected according to the application purpose. There is no special limitation on the structure other than the anode catalyst layer, and the optimal composition can be selected according to the purpose. It should be noted that the catalyst involved in the invention can also be used as a catalyst on the cathode catalyst layer side.
[0072] The anode catalyst layer is prepared by controllably modifying a precious metal-based porous carbon catalyst with cerium oxide, and a hydrogen fuel cell is prepared using the catalyst layer. After the endurance test under idling conditions, the increase in the hydrogen leakage current density of the proton exchange membrane used is reduced, and the increase in the proton conduction resistance of the catalyst layer is reduced. It can be considered that the reason is that during the endurance process, the dissolution and migration of cerium ions will affect the loss of its free radical elimination effect, and the sulfonate groups of the perfluorosulfonic acid polymer exchange ions with the dissolved cerium ions, affecting the proton conduction ability. By restricting the cerium oxide particles in the pore structure of the precious metal-based porous carbon catalyst, the migration of the cerium oxide particles is avoided and the dissolution is slowed down. In addition, the cerium oxide is close to the free radical generation site, which can eliminate the free radicals generated in the power generation reaction in real time, further improving the stability and service life of the fuel cell.
[0073] Specific embodiments and comparative examples of the present invention are described below:
[0074] 1. Preparation of catalyst
[0075] 1.1. Example 1
[0076] 0.2g of cerium nitrate hexahydrate was fully dissolved in 50mL of deionized water by stirring, and 0.35g of platinum-based porous carbon catalyst was added, with a platinum loading of 50%. Stirring was continued in this state to make the system uniformly dispersed. The reaction system was sealed, vacuumed for 3min, and nitrogen was replaced for 3min and repeated three times, and the vacuum degree was adjusted to -0.05MPa, and the vacuum degree was maintained throughout the reaction process. Under stirring, 1mol / L sodium hydroxide solution was added dropwise, the pH was adjusted to 13, and the addition was completed within 30min to obtain a mixed dispersion, and the reaction system was warmed to 50°C and the reaction was continued for 30min. After the system after the reaction was cooled to room temperature, a filter membrane (Whatman7182-002, 0.2μm) was used for suction filtration to separate the catalyst from the reaction solution and collect the final product. For the removal of weakly durable ionic components, the filter residue was washed three times with deionized water under continuous vacuum filtration (vacuum degree: -0.05MPa), the filtrate was neutral, the resistivity of the filtrate was >18.3MΩ·cm, and the filter residue was separated. For the removal of weakly durable non-ionic components, 50mL of deionized water was added to the obtained filter residue, and after applying ultrasound for 10 minutes, mechanical stirring was performed for 10 minutes to separate the weakly durable non-ionic components from the catalyst into the water. Under continuous vacuum filtration (vacuum degree: -0.05MPa), the filter residue was washed three times with deionized water to complete the treatment steps. After drying in a vacuum oven at 60°C for 24 hours, a cerium oxide controllably modified platinum-based porous carbon catalyst was obtained under the protection of a nitrogen atmosphere.
[0077] 1.2. Example 2
[0078] The difference between this embodiment and embodiment 1 is that the carbon catalyst used is a platinum-based solid carbon catalyst, and the rest is the same as embodiment 1 and will not be repeated here.
[0079] 1.3 Comparative Example 1
[0080] A platinum-based porous carbon catalyst not supported by cerium oxide is directly used for preparing a fuel cell membrane electrode, and the platinum loading is 50%.
[0081] 2. Preparation of fuel cells
[0082] 2.1. Example 3
[0083] The preparation of the fuel cell of this embodiment includes the following steps:
[0084] Step 1: Preparation of Catalytic Layer
[0085] The catalyst prepared in Example 1 was used to prepare the anode catalyst layer. The ionomer used was a 25% Aquivion solution commercialized by Solvay (a perfluorosulfonic acid PFSA ionomer dispersion, trade name: D79-25BS, ion exchange equivalent of 790 g / mol; the solvent was a mixed solution of water and isopropanol, the water-to-alcohol mass ratio was 1.3:1, the slurry solid content was 10%, the I / C ratio (the mass ratio of the ion exchange resin to the catalyst in the catalyst layer) was set to 1, and the anode slurry was obtained after mechanical stirring and uniform dispersion. The platinum-cobalt catalyst commercialized by TKK (trade name 36E52, platinum loading 46%) was used as the cathode catalyst, and the ionomer, solvent, and water-to-alcohol ratio were all consistent with the anode slurry, the slurry solid content was 15%, and the I / C ratio was set to 1.1. The scraper coating process was adopted, and the wet film thickness was controlled by controlling the scraper head spacing, and the preparation of the catalyst layer was completed after drying. The platinum loading of the anode catalyst layer was 0.03 mg / cm 2 The platinum-cobalt loading of the cathode catalyst layer is 0.18 mg / cm 2 .
[0086] Step 2: Membrane electrode assembly
[0087] The proton exchange membrane used was a 10 μm membrane produced by Shandong Dongyue Group. The anode side catalyst layer and the cathode side catalyst layer prepared in step 1 were transferred to both sides of the proton exchange membrane respectively. The gas diffusion layer, gold-plated current collector, and graphite parallel flow field plate (using channels and ribs with a width and depth of 0.4 mm) were assembled in sequence to complete the preparation of a single fuel cell. The tested activity range was 1 cm×2 cm.
[0088] 2.2. Example 4
[0089] The difference between this embodiment and embodiment 3 is that the anode side catalyst layer in this embodiment is made using the catalyst prepared in embodiment 2, and the rest of this embodiment is the same as embodiment 3 and will not be repeated here.
[0090] 2.3 Comparative Example 2
[0091] The difference between this comparative example and Example 3 is that, in this comparative example, when the catalyst prepared in Comparative Example 1 is used to prepare the anode side catalyst layer slurry, in addition to the catalyst, a cerium oxide dispersion (the mass fraction of cerium oxide is 20%) is added, and the mass ratio of the dispersion to the added catalyst is 1:1. The rest is consistent with Example 3 and will not be repeated here.
[0092] 2.4 Comparative Example 3
[0093] The difference between this comparative example and Example 1 is that the anode side catalyst layer in this comparative example is made using the catalyst prepared in Comparative Example 1, and the rest of this comparative example is the same as Example 3 and will not be repeated here.
[0094] 3. Validation of the embodiments of the present invention:
[0095] 3.1. First, the characterization test method used in the present invention is described:
[0096] 3.1.1. For the prepared catalyst, the characterization test method used is:
[0097] 1) Element mass ratio
[0098] The x-ray photoelectron spectrum (XPS) of the supported catalyst was measured, and the mass proportion of each element was quantified based on the spectrum integration.
[0099] 2) Pore diameter, pore volume and BET specific surface area
[0100] The nitrogen adsorption isotherms of the catalysts before and after loading were measured, and the pore diameter, pore volume and BET specific surface area were calculated based on the obtained nitrogen adsorption isotherms.
[0101] 3) Loading ratio in the hole
[0102] The loading ratio inside the pore can be obtained by scanning the element surface in the transmission mode of a scanning transmission microscope to obtain the amount of cerium element, and then obtaining the amount of cerium element outside the pore by scanning the element surface in the secondary mode, thereby obtaining the distribution ratio of cerium oxide inside and outside the pore.
[0103] 3.1.2. For the prepared fuel cell, the characterization test method used is:
[0104] 1) Durability test
[0105] Refer to the DOE recommended procedures to carry out the idle condition durability test evaluation. The test conditions are: hydrogen atmosphere at the anode, flow rate of 1L / min, air atmosphere at the cathode, 1L / min, single cell temperature of 90°C, humidification of 30%RH (relative humidity) for both cathode and anode gas atmospheres, anode back pressure of 150kPa (gauge pressure), and cathode back pressure of 100kPa (gauge pressure).
[0106] The initial membrane electrode sample was kept in open circuit condition for 45 hours as one cycle. After each cycle, the power generation performance test, hydrogen leakage current density test and catalyst layer proton conductivity test were carried out to comprehensively evaluate the attenuation of the membrane electrode during the durability test. During the durability test, the open circuit potential change was continuously monitored.
[0107] 2) Hydrogen leakage current density test
[0108] The hydrogen leakage current density was measured by linear voltammetry from open circuit to 0.6 V at a scan rate of 20 mV / s. The test conditions were: hydrogen atmosphere at the anode with a flow rate of 0.07 L / min, nitrogen atmosphere at the cathode with a flow rate of 0.166 L / min, single cell temperature of 80°C, humidification of both the anode and cathode gas atmospheres at 90% RH, and a back pressure of 0 (gauge pressure).
[0109] 3) Proton conduction resistance test
[0110] At 0.45 V, the constant potential impedance spectrum was measured with a voltage excitation of 10 mV and a measurement frequency range of 100 kHz to 500 mHz. The test conditions were: a hydrogen atmosphere at the anode with a flow rate of 0.07 L / min, a nitrogen atmosphere at the cathode with a flow rate of 0.166 L / min, a single cell temperature of 80°C, and humidification of both the anode and cathode gas atmospheres at 90% RH, with a back pressure of 0 (gauge pressure).
[0111] 4) Power generation performance
[0112] The voltage values at different current points were measured in the constant current mode to evaluate the power generation performance of the fuel cell. Test conditions: the anode was hydrogen atmosphere, 1L / min flow, the cathode was air atmosphere, 2L / min, the single cell temperature was 80°C, the anode and cathode gas atmospheres were both humidified at 90% RH, and the back pressure was 70kPa (gauge pressure)
[0113] 3.2. The various embodiments and comparative examples of the present invention were tested according to the characterization test method described in 3.1. The test results are as follows:
[0114] 3.2.1. Catalysts prepared
[0115] 1) Element mass ratio
[0116] Figure 1 The XPS images of Example 1 and Example 2 for preparing the anode side catalyst layer are shown, and the mass percentage of each element is obtained by calculating the XPS image. Figure 1 Figures a and b in the figure are the full spectrum results of Example 1 and the fine spectrum of Ce element, respectively. Figure 1 Figures c and d in the figure are the full spectrum results of Example 2 and the fine spectrum of Ce element, respectively. Figure 1 The following can be known:
[0117] (1) Both Example 1 and Example 2 contain cerium element after loading, indicating successful loading of cerium oxide;
[0118] (2) The mass ratio of platinum to carbon in Example 1 is 0.93:1, and the mass ratio of cerium to carbon is 0.35:1;
[0119] (3) The mass ratio of platinum to carbon in Example 2 is 1.06:1, and the mass ratio of cerium to carbon is 0.33:1.
[0120] 2) Pore diameter, pore volume and BET specific surface area
[0121] Figure 2 The isothermal nitrogen adsorption and desorption images, pore size, pore volume and BET specific surface area of Example 1 used for preparing the anode catalyst layer before and after loading are shown. The following can be known:
[0122] (1) The BET specific surface area of Example 1 before loading is 318.99 m 2 / g, and the BET specific surface area after loading was reduced to 293.14 m 2 / g, which is due to the attachment of cerium oxide to the catalyst, which reduces the BET specific surface area;
[0123] (2) The pore size after loading in Example 1 decreased from 9.88 nm to 9.64 nm, indicating that cerium oxide was also partially loaded in the pores;
[0124] (3) The pore volume of the sample after loading in Example 1 increased from 0.54m 3 / g reduced to 0.45m 3 / g, further indicating that cerium oxide is distributed in the pores.
[0125] 3.2.2 Application of fuel cells
[0126] 1) Durability test
[0127] Figure 3 The decay rates of the open circuit potential before and after endurance test are shown for Example 3 and Example 4, Comparative Example 2 and Comparative Example 3. The following can be seen:
[0128] (1) According to the attenuation rate evaluation, the lower the attenuation rate, the better the durability effect, Example 3 is the best, Example 4 is the second, Comparative Example 2 is the third, and Comparative Example 3 is the worst;
[0129] (2) All samples loaded with cerium oxide have a certain durability improvement effect, and the durability improvement effect of cerium oxide loaded in the pores is the best.
[0130] 2) Hydrogen leakage current density test
[0131] Figure 4 The changes in hydrogen leakage current density at the start and end of durability are shown for Example 3, Example 4, Comparative Example 2, and Comparative Example 3, and the following can be known:
[0132] (1) At the endurance starting point, the hydrogen leakage current density of each sample is similar, indicating that the addition of cerium oxide has no significant effect on the initial hydrogen leakage current density of the proton exchange membrane;
[0133] (2) Durability endpoint, evaluated by percentage change, the smaller the increase, the better the durability effect, Example 3 is the best, Example 4 is the second, Comparative Example 2 is the third, and Comparative Example 3 is the worst; this indicates that the samples loaded with cerium oxide all have a certain durability improvement effect, and the durability improvement effect of cerium oxide loaded in the pores is the best.
[0134] 3) Proton conduction resistance test
[0135] Figure 5 The changes in the proton conduction resistance of the catalyst layer at the start and end of the durability are shown in Example 3, Example 4, Comparative Example 2, and Comparative Example 3, and the following can be known:
[0136] (1) At the endurance starting point, the proton conduction resistance of the catalyst layer of each sample is similar, indicating that the addition of cerium oxide does not affect the proton conduction capacity of the catalyst layer;
[0137] (2) Durability endpoint, the proton conduction resistance of the catalytic layer, is evaluated according to the percentage change. The smaller the increase value, the less the proton conduction capacity deteriorates. Comparative Example 3 is the best, followed by Example 3, Comparative Example 2 is the third, and Example 4 is the worst. This shows that the proton conduction capacity of the samples supported by cerium oxide will be affected to a certain extent, but cerium oxide is supported in the pores, which helps to reduce the dissolution and migration of cerium oxide and reduce the poisoning of the ionomer.
[0138] 4) Power generation performance test
[0139] Figure 6 The polarization curve changes at the start and end of the durability test are shown for Example 3, Example 4, Comparative Example 2, and Comparative Example 3, and the 1A / cm 2 The voltage value is summarized in Figure 7 In the above, we can know the following contents:
[0140] (1) Durability starting point, each sample is at 1A / cm 2 The voltage values under are close, indicating that the addition of cerium oxide does not cause serious deterioration of fuel cell performance;
[0141] (2) Durability end point, each sample at 1A / cm 2 The voltage value under the condition is evaluated according to the percentage change. The less it decreases, the better the durability effect is. Example 3 is the best, Comparative Example 2 is the second, Example 4 is the third, and Comparative Example 3 is the worst. This shows that the samples with cerium oxide support all have a certain durability improvement effect, and the durability improvement effect of cerium oxide support in the pore is the best.
[0142] In summary, the present invention achieves a controllable proportion of cerium oxide particles confined in the pore structure of the precious metal-based porous carbon catalyst, thereby avoiding the migration of cerium oxide particles and slowing down the dissolution. Moreover, cerium oxide is close to the free radical generation site and can eliminate the free radicals generated in the power generation process in real time, effectively improving the stability and service life of the fuel cell.
[0143] Although the embodiments of the present invention have been described in detail above, the present invention is not limited to the above embodiments, and various modifications can be made without departing from the gist of the present invention.
Claims
1. A cerium oxide controllably modified noble metal-based porous carbon catalyst, characterized in that: Cerium oxide particles are loaded in the pores and outside the pores of the porous carbon, respectively. The cerium oxide particles loaded in the pores are not less than 40% of the total loading amount of the cerium oxide particles in the porous carbon catalyst. The cerium / carbon mass ratio loaded in the porous carbon catalyst is 0.2:1 to 0.5:
1. The pore volume of the porous carbon used for loading is 0.4 cm 3 / g~1cm 3 / g.
2. The porous carbon catalyst according to claim 1, characterized in that The noble metal-based particles are selected to provide electrochemical reaction activity.
3. The porous carbon catalyst according to claim 1, characterized in that The material of the noble metal-based particles is any one of the following: Any noble metal or alloy of multiple noble metals; Alloys containing a noble metal element and at least one non-noble metal element; Noble metal oxynitrides.
4. A method for preparing the porous carbon catalyst according to any one of claims 1 to 3, characterized in that: include: In the first step, the cerium source precursor and the noble metal-based porous carbon catalyst are fully dispersed and impregnated in the porous carbon pores; In the second step, the cerium source is reacted inside and outside the pores of the porous carbon to generate cerium oxide, thereby completing the loading; The third step is to separate and purify the modified catalyst from the reaction solution to obtain the cerium oxide controllably modified noble metal-based porous carbon catalyst.
5. The preparation method according to claim 4, characterized in that: The impregnation step in the first step is carried out in an inert atmosphere and a set vacuum degree is maintained, and / or The vacuum degree is set at -0.1MPa to -0.02MPa.
6. The preparation method according to claim 4, characterized in that: The second step specifically comprises: adding alkaline solution dropwise under stirring to adjust the pH to obtain a mixed dispersion, and reacting the cerium source inside and outside the pores of the porous carbon at a preset reaction temperature to generate cerium oxide to complete the loading; and / or pH controlled at 10-14; and / or The preset reaction temperature is set at 30°C to 70°C.
7. The preparation method according to claim 4, characterized in that: The third step specifically comprises: filtering the product obtained in the second step, removing weakly durable ionic components, removing weakly durable non-ionic components, and drying to obtain the cerium oxide controllably modified noble metal porous carbon catalyst; The weakly durable ion components are unreacted ionic substances on the catalyst surface and ionic substances generated during the oxide generation process; The weakly durable non-ionic component is cerium oxide attached to the outside of the porous carbon pores and easily falling off, and cerium oxide particles not attached to the porous carbon.
8. The preparation method according to claim 7, characterized in that: The removal of the weakly durable ionic components and the removal of the weakly durable non-ionic components are both carried out by a combined treatment method of deionized water washing and vacuum filtration.
9. The preparation method according to claim 8, characterized in that: The removal of the weakly durable non-ionic components also includes applying mechanical vibration and stirring without damaging the catalyst particles.
10. A hydrogen fuel cell, characterized in that: The hydrogen fuel cell comprises an electrode catalyst layer, wherein the electrode catalyst layer comprises the porous carbon catalyst according to any one of claims 1 to 3 and / or the porous carbon catalyst produced by the production method according to any one of claims 4 to 9.
Citation Information
Patent Citations
Porous carbon supported platinum-cerium oxide catalyst for fuel cell and preparation thereof
CN101185891A
Synthetic method of quantum dot cerium oxide / modified cerium oxide nanophase materials
CN106745166A
Deodorant and preparation method thereof
CN108211779A
Spraying construction method and equipment for removing indoor decoration pollution by utilizing hydroxyl
CN111545060A
Method for inhibiting shuttle effect of lithium-sulfur battery by using cerium dioxide-doped porous carbon rod
CN113964319A